Robust Speed Controller Design Using H_infinity Theory for High-Performance Sensorless Induction Motor Drives - Ahmed A. Zaki Diab; Abou-Hashema M. El-Sayed; Hossam Hefnawy Abbas; Montaser Abd El Sattar (Energies, 2019)
In this paper, a robust speed control scheme for high dynamic performance sensorless induction motor drives based on the H_infinity (H) theory has been presented and analyzed. The proposed controller is robust against system parameter variations and achieves good dynamic performance. In addition, it rejects disturbances well and can minimize system noise. The H controller design has a standard form that emphasizes the selection of the weighting functions that achieve the robustness and performance goals of motor drives in a wide range of operating conditions. Moreover, for eliminating the speed encoder—which increases the cost and decreases the overall system reliability—a motor speed estimation using a Model Reference Adaptive System (MRAS) is included. The estimated speed of the motor is used as a control signal in a sensor-free field-oriented control mechanism for induction motor drives. To explore the effectiveness of the suggested robust control scheme, the performance of the control scheme with the proposed controllers at different operating conditions such as a sudden change of the speed command/load torque disturbance is compared with that when using a classical controller. Experimental and simulation results demonstrate that the presented control scheme with the H controller and MRAS speed estimator has a reasonable estimated motor speed accuracy and a good dynamic performance.